The role of IT mindfulness in digital technostress and intention to use fintech in Indonesia - Santi Putriani; Sinta Putriana (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study aims to investigate how IT mindfulness and digital technostress affect the Y and Z generation of consumers' intentions to adopt Fintech in Indonesia.Design/Methodology/Approach: Consumer respondents from Indonesia's Y and Z generations were selected in this study. SEM-PLS was employed to examine the 309 respondents. Research findings: The study suggested that while IT mindfulness could decrease the adverse effects of digital technostress on the intention to use Fintech and increase it, digital technostress did not influence the intention to use Fintech.Theoretical contribution/Originality: This is the first study to examine how IT mindfulness and digital technostress affect customers in Indonesian Y and Z generation’s intention to use Fintech. The findings of this study add to the body of knowledge on IT mindfulness and will guide future research in this area and also be helpful to innovators and decision-makers in the field of financial technology so that consumers will continue to use it and, ultimately, support sustainable development.